2019
DOI: 10.31014/aior.1992.02.01.67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Discipline and Work Environment on the Performance of AL Hudori Cooperative of Palembang Employees

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…WEV also directly affected how well a job was performed. Hidayati et al (2019), Liestiani and Perizade (2019) and Idris et al (2020) demonstrated that WEV had an important impact on employees' performance. Furthermore, creating a professional WEV for performance was critical to maintaining an adequate nursing workforce (Shirey, 2017).…”
Section: The Mediating Role Of Work Engagementmentioning
confidence: 97%
See 1 more Smart Citation
“…WEV also directly affected how well a job was performed. Hidayati et al (2019), Liestiani and Perizade (2019) and Idris et al (2020) demonstrated that WEV had an important impact on employees' performance. Furthermore, creating a professional WEV for performance was critical to maintaining an adequate nursing workforce (Shirey, 2017).…”
Section: The Mediating Role Of Work Engagementmentioning
confidence: 97%
“…As nurse managers' actions directly impacted a clinic's nursing staff, they either improved or worsened the standards of nursing services delivered. In addition, a favorable WEV fostered moral and intellectual motivation to ensure the quality of work and development of mutual trust between nurses and their superiors (Hidayati et al, 2019;Liestiani and Perizade, 2019). The goal of improving nurses' performance is to bring change and foster connections of support, inspiration and empathy, which leads to enhanced job satisfaction, morale, teamwork, productivity and engagement with common goals (Laschinger et al, 2002;Idris et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rudini Raya Lambe dan Herry Wihasnanto sirkulasi udara yang baik, tata warna ruangan tidak mengganggu pandangan dalam bekerja, dekorasi ruangan kerja membuat nyaman, adanya music yang berirama lembut menambah semangat bekerja, suhu udara sudah nyaman untuk bekerja, kebisingan suara tidak menggangu untuk bekerja, karyawan merasa aman dalam bekerja, adanya hubungan yang harmonis antara atasan dengan bawahan dalam bekerja dan sesama rekan kerja terjalin hubungan yang baik serta nyaman. Hasil penelitian ini sesuai dengan penelitian yang dilakukan oleh Liestiani, et al, (2019) dan Putra dan Liswani (2020), yaitu menganalisis pengaruh lingkungan kerja terhadap kinerja karyawan.…”
Section: Jurnal Ekonomi Dan Industriunclassified
“…Iklim organisasi adalah kualitas lingkungan internal yang relatif berlangsung lama, yang dialami oleh anggota organisasi, mempengaruhi perilaku setiap anggota (Glisson, 2015). Beberapa hasil penelitian melaporkan bahwa variabel iklim kerja berpengaruh terhadap kinerja (Rahsel, 2016), dan terdapat pengaruh Variabel disiplin kerja dan lingkungan kerja terhadap kinerja karyawan (Liestiani et al, 2019). Syelviani (2017) melaporkan bahwa ada pengaruh yang signifikan antara deskripsi kerja terhadap kinerja pegawai negeri sipil dengan nilai adjusted R square 72% yang artinya sebanyak 28% kinerja pegawai dipengaruhi oleh faktor lain.…”
Section: Tabel 1 Tanggapan Responden Tentang Kuantitas Pekerjaanunclassified